2015
DOI: 10.1024/1421-0185/a000161
|View full text |Cite
|
Sign up to set email alerts
|

The Facilitating Effect of Need-Supportive Parenting on the Change Rate and Adaptation of Dual Autonomy Among Taiwanese Adolescents

Abstract: Abstract. Two empirical studies were conducted to test the facilitating effect of need-supportive parenting (NSP) on Taiwanese adolescents’ individuating autonomy (IA) and relating autonomy (RA) as well as to investigate the mediating effect of IA and RA on the relationship between NSP and adaptation. Study 1 adopted a cross-sectional design and found that (1) NSP was positively related to adolescents’ IA and RA capacity; and (2) the positive effects of NSP on intrapersonal adaptation (i.e., self-esteem and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Individuating autonomy and relating autonomy can coexist within an individual and may co-promote individuals’ psychological adaptation and well-being. DAM further proposed the Domain Superiority Hypothesis, which states that individuating autonomy is more strongly associated with intrapersonal domain variables, while relating autonomy is more associated with interpersonal domain variables (Yeh and Yang, 2006; Yeh et al, 2009; Wu et al, 2015). FP represents a parent-child interaction pattern between parents and children (Bedford and Yeh, 2019), and thus belongs to interpersonal domain variable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuating autonomy and relating autonomy can coexist within an individual and may co-promote individuals’ psychological adaptation and well-being. DAM further proposed the Domain Superiority Hypothesis, which states that individuating autonomy is more strongly associated with intrapersonal domain variables, while relating autonomy is more associated with interpersonal domain variables (Yeh and Yang, 2006; Yeh et al, 2009; Wu et al, 2015). FP represents a parent-child interaction pattern between parents and children (Bedford and Yeh, 2019), and thus belongs to interpersonal domain variable.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike SDT, DAM regards autonomy as an adaptive capacity that includes cognitive, functional, and emotional elements. It also differentiates two forms of autonomy: individuating autonomy and relating autonomy/inclusive autonomy (Gore and Cross, 2006; Yeh and Yang, 2006; Wu et al, 2015). Individuating autonomy is oriented toward acting volitionally by expressing individualistic attributes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar finding was reported in non-Western populations, such as Taiwanese populations. The study found the effect of need-supportive parenting on intrapersonal and interpersonal adaptation was mediated by need satisfaction ( Wu et al, 2015 ). These findings might be expected as the SDT suggests the notion applied universally.…”
Section: Introductionmentioning
confidence: 99%